Pengaruh size company, profitabilitas, dan likuiditas terhadap tax avoidance dengan struktur modal sebagai variabel intervening pada Bank Umum Syariah di Indonesia - Devi, Novita Shinta; Arinta, Yusvita Nena (Nur Science Institute, 2021)
The purpose of this study was to determine the effect of company size, profitability, and liquidity on tax avoidance with capital structure as an intervening variable. The data used in this research are quantitative data and path analysis as data analysis. This study uses panel data. The population in the study were all Islamic Commercial Banks registered with the OJK (Financial Services Authority) for the 2016–2020 period, namely 14 Islamic Commercial Banks. The samples taken in the study were 10 Islamic Commercial Banks using a purposive sampling technique. This study shows that company size and capital structure are insignificant, while profitability and liquidity positively affect tax avoidance. The capital structure cannot mediate the effect of company size, profitability, and liquidity on tax avoidance. However, simultaneously, the size of the company’s profitability, liquidity, and capital structure affects tax avoidance.